Total Infrapatellar Fat Pad Excision Leads to Worse Isokinetic Performance in Total Knee Arthroplasty: A Randomized Controlled Trial - Cankaya, Deniz; Akti, Sefa; Yasar, Niyazi Erdem; Karakus, Dilek; Unal, Kazim Onur; Karhan, Taha Esref; Sezgin, Erdem Aras (The Journal of Knee Surgery, 2021)
There are concerns that total infrapatellar fat pad (IPFP) excision in total knee arthroplasty (TKA) results in patellar tendon shortening due to ischemic contracture, but individual preference of the surgeon is still the main determinant between total or partial excision. The aim of this randomized controlled study was to compare isokinetic performance and clinical outcome of TKAs with total and partial excision of the IPFP. Seventy-two patients scheduled to undergo TKA for primary knee osteoarthritis by a single surgeon were randomly assigned to either total or partial excision group. Patients were evaluated preoperatively and at postoperative 1 year, with Knee Society Score (KSS) and isokinetic measurements. The physiatrist performing isokinetic tests and patients were blinded to the study. There were no significant differences between the groups in respect of age, body mass index, gender, and preoperative KSS and isokinetic performance. Postoperatively, both groups had improved KSS knee and KSS function scores, with no difference determined. Knee extension peak torque was significantly higher postoperatively in the partial excision group at postoperative 1 year (p = 0.036). However, there were no significant differences in knee flexion peak torque following TKA (p = 0.649). The results of this study demonstrated that total excision of the IPFP during TKA is associated with worse isokinetic performance, which is most likely due to changes in the knee biomechanics with the development of patella baja. Partial excision of the IPFP appears to be a valid alternative to overcome this potential detrimental effect without impeding exposure to the lateral compartment. This is a Level I, therapeutic study.
Keywords: infrapatellar fat pad; patellar tendon; total knee arthroplasty; isokinetic test